i need help with this.
Attachments:
![](https://hi-static.z-dn.net/files/d90/72f9af9f9d63a06f5237d23add893512.jpg)
Answers
Answered by
2
24 is the answer i think
kshitij064:
no
Answered by
2
let the no of chocolate in box be x then no. of eaten chocolate be x/3 .
then left chocolate in the box be total -eaten chocolate which is x - x/3 and it is equal to 16.
x -x/3=16
2x/3=16
2x=16*3
2x=48
x=48/2
x=24
I think it will helps u
then left chocolate in the box be total -eaten chocolate which is x - x/3 and it is equal to 16.
x -x/3=16
2x/3=16
2x=16*3
2x=48
x=48/2
x=24
I think it will helps u
Similar questions